2008
DOI: 10.1111/j.1600-0714.2008.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

A case–control study on etiological factors involved in patients with burning mouth syndrome

Abstract: OBJECTIVE: To evaluate and analyze the risk factors for burning mouth syndrome (BMS). METHODS: Eighty-seven consecutive patients with BMS and a randomly selected control group (n = 82) were comprehensively investigated with a self-designed questionnaire, Self-rating Anxiety Scale (SAS) and Self-rating Depression Scale (SDS). A complete blood count and serum sex hormone were also examined in patients with BMS and control subjects. All the data obtained were transferred to a data bank and analyzed statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
99
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 22 publications
7
99
2
2
Order By: Relevance
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…This datum may point that both BMS and dry mouth seem to affect mainly the population aged 50 years or around (1,15,24) . Regarding patients' clinical history, the symptomatic groups showed similarities in may aspects, which agrees with the reviewed literature (2,(4)(5)(6)(7)(8)11,16,22,23) . Some studies, however, found variations especially regarding the intensity of the symptom (4,22,24) .…”
Section: Discussionsupporting
confidence: 77%
“…Strategies employed to minimize oral discomfort in both symptomatic groups most patients with burning mouth (1)(2)(3)(4)(5) and dry mouth (15,19,24,29) complaints are female. Control Group was paired as to gender, in order to avoid biases regarding this variable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations